1991
DOI: 10.1148/radiology.179.2.2014304
|View full text |Cite
|
Sign up to set email alerts
|

Apparent avascular necrosis of the hip: appearance and spontaneous resolution of MR findings in renal allograft recipients.

Abstract: The sensitivity of magnetic resonance (MR) imaging in the detection of avascular necrosis (AVN) of the hip and natural history of the MR findings were determined prospectively in renal allograft recipients, a group at risk for development of the disease. One hundred four patients were studied up to 24 months after transplantation. In 25 hips in 14 patients, MR findings were consistent with AVN. Pain developed in seven hips in four patients; in each hip, the MR images showed abnormality before the onset of symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 0 publications
2
50
0
2
Order By: Relevance
“…As in previous studies these changes regressed within 3 months and the MR scans became normal (5). This is not the case with AVN, as an abnormal signal in AVN takes many months to resolve (10).…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies these changes regressed within 3 months and the MR scans became normal (5). This is not the case with AVN, as an abnormal signal in AVN takes many months to resolve (10).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hernigou et al [9] reported pain developed in 91% and collapse had occurred in 77% in asymptomatic ON associated with sickle cell disease. However, several investigators [5,17,21] have shown using MRI certain small lesions spontaneously heal and decrease in size over time.…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers have reported ON of the femoral head generally has a progressive course of collapse once changes are apparent radiographically [1,12,24]. However, asymptomatic hips in the early stage of ON have variable paths of disease progression [13,14,17,22,24,29]. Ito et al [13] observed there was no difference in occurrence of progression between hips with Steinberg Stage I disease and hips with Stage II disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion P revious studies of asymptomatic osteonecrosis of the femoral head have demonstrated various rates of disease progression 5,[20][21][22][23][24][25][26][27][28] . Differing opinions regarding the fate of asymptomatic disease have been attributed to several reasons, including differences in study populations, diagnostic modalities, follow-up periods, and the definition of disease progression 5,27 .…”
Section: Fat E O F U N T R E At E D Asymptomatic O S T E O N E C R O mentioning
confidence: 99%